Governance of metropolitan areas for delivery of public services in Latin America - Alejandra Berenice Trejo Nieto; José Luis Ni\~no Amezquita; María Luisa Vasquez (REGION, 2018)
One of the key issues at metropolitan level is the provision of public services and this paper highlights the importance of understanding the governance of public services in the context of increasing urbanization and decentralization.~This paper provides a comparative analysis on metropolitan governance in Latin America by analysing specific case studies. The objective is to identify how the governance setting in metropolitan areas shapes the process anthe results of providing public services to wider population. We examine metropolitan governance by employing a 3x3x3 model as a framework for addressing key issues about urban services delivery. Bogota, Lima and Mexico City are the metropolitan areas selected. Secondly, we focus on three sectors: transport, solid waste collection and water. Finally, the analysis focuses in three aspects of governance: coordination, financial sustainability and coverage and quality. The data collection process involved field research in Bogota, Lima and Mexico City.
Keywords: 330